A bibliometric data analysis of multi-criteria decision making methods in heritage buildings - Morkūnaitė, Žydrūnė; Kalibatas, Darius; Kalibatienė, Diana (Journal of Civil Engineering and Management, 2019)
Numerous countries are trying to find the best solution for conservation, restoration or reuse of the heritage buildings, preserving their cultural, historical, ethnic and spiritual values. The scientists, researchers and government are analysing the problems concerning with heritage building’s, like seismic issues, energy saving, sustainability, structures, materials and adaptive reuse. Since, heritage buildings’ reuse and preservation are characterized by multiple criteria, a multi-criteria decision making (MCDM) methods are useful in finding rational solutions for the previously mentioned problems. The current paper aims to overview papers on the MCDM approaches application in regard to heritage buildings’ reuse and preservation area. This study employs a bibliometric data analysis to explore state-of-the-art of the defined topic and an in-deep analysis – to synthesize the knowledge domain and critically evaluate a thorough literature in the analysed topic. As a result, scientific maps were created to reveal the knowledge domain of MCDM approaches in heritage buildings’ reuse and preservation. Finally, research gaps and future research directions are identified. Results of the analysis shows that till now MCDM approaches are not widely used in solving heritage buildings reuse and preservation issues. Moreover, there is luck of complex problem solving approach in cultural heritage buildings area.